Polythiophene nanocomposites for photodegradation applications: Past, present and future - Ansari, Mohd Omaish; Khan, Mohammad Mansoob; Ansari, Sajid Ali; Cho, Moo Hwan (Journal of Saudi Chemical Society, 2015)
Polythiophene (PTh) has been the subject of considerable interest because of its good environmental stability, unique redox electrical behavior, stability in doped or neutral states, ease of synthesis, and wide range of applications in many fields. Apart from its applications in the electrical or electronic field, PTh has shown promising applications in photocatalytic degradation. The fabrication of a catalyst, metal oxides with PTh, extends the absorption range of the modified composite system, thereby enhancing the photocatalytic activity under UV or visible light irradiation. Substituted PTh, such as alkyl substitution, modifies the electronic properties of the polymer, thereby enlarging the potential for industrial applications. PTh or substituted PTh when combined with metal, metal oxide or a combination of both, can exhibit tailorable photocatalytic properties. This review focuses on the chemistry of the band gap engineering of PTh or PTh based systems and the mechanism of photocatalytic degradation. The major developments in the field of UV and visible light-assisted photocatalysis are discussed in terms of the parameters that affect the photocatalytic efficiency. On the other hand, some challenges still needs to be investigated experimentally, which are mentioned as the scope for future studies. For simplicity, the review has been classified under a major subheading depending on the type of composite system used for photocatalysis.